Repair of Alar Defects Using the Alar Rotation Flap: Our Experience with 394 Patients. Issue 1 (2nd October 2020) - Mitkov, Mario; Griffith, James; Dyson, Mary; Kimyai-Asadi, Arash
Abstract : Background: The purpose of this study was for the authors to describe their patient selection, surgical technique, and results with the alar rotation flap for surgical defects of the nasal ala. Methods: The authors performed a retrospective analysis of all alar rotation flaps performed between June of 2006 and February of 2019. Three hundred ninety-four patients were identified, and follow-up encounters were reviewed to assess for complications and need for revision procedures. Results: The alar rotation flap was performed on 394 patients over a 13-year period. The mean defect size was 9.3 ± 2.8 mm by 7.2 ± 2.3 mm. Three hundred nineteen patients (81 percent) were evaluated postoperatively, with a mean average duration of follow-up of 2.3 years (range, 6 days to 11.9 years). Complications included hemorrhagic crust along the incision line [ n = 9 (3 percent)], flap edema [ n = 7 (2 percent)], internal nasal valve dysfunction [ n = 3 (1 percent)], depressed surgical scar [ n = 2 (1 percent)], hematoma [ n = 1 (0.5 percent)], and paresthesia [ n = 1 (0.5 percent)]. Conclusion: The alar rotation flap is a reliable one-stage flap for small- to medium-size partial-thickness defects of the nasal ala that can produce topographic restoration with minimal risk of aesthetic or functional complication. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.